A facile route for preparation of CdS nanoparticles - Maleki, M.; Sasani Ghamsari, M.; Mirdamadi, Sh.; Ghasemzadeh, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
CdS nanoparticles have been synthesized by a chemical reaction route using
ethylenediamine as a complexing agent. The nanoparticles were characterized using
techniques such as X-ray powder diffraction (XRD), scanning electron microscope
(SEM), UV–VIS absorption spectroscopy, and photoluminescence spectroscopy. The
absorption edge for the bulk hexagonal CdS is at 512 nm (2.42 eV). Comparing with the
bulk CdS, it is believed that the blue shift in the absorption peak was caused by the
quantum confinement effect. Photoluminescence measurements indicate CdS
nanoparticles show fluorescence band with a maximum close to 315 nm.